1999
DOI: 10.1007/s002619900536
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional endoluminal ultrasound: a new method for the evaluation of gastrointestinal tumors

Abstract: Three-dimensional display and the ability to review endoluminal ultrasound data interactively may improve the staging of gastrointestinal tumors. These preliminary data encourage further evaluation of this technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 9 publications
0
10
0
2
Order By: Relevance
“…In 3D-ES using high-frequency probes, a fuzzy image may occur because of tissue movements during the cardiac cycle. Hunerbein et al [21] deserve credit for pinpointing the value of using electrocardiographic (ECG) triggering during acquisition of US images of the upper GI tract. Molin et al [25] also concluded that ECG triggering during 3D-ES acquisition increased image resolution by reducing tissue dislocation caused by cardiac movements and resulted in improved accuracy in evaluation of smaller superficial lesions in the upper GI tract.…”
Section: Abdominal Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…In 3D-ES using high-frequency probes, a fuzzy image may occur because of tissue movements during the cardiac cycle. Hunerbein et al [21] deserve credit for pinpointing the value of using electrocardiographic (ECG) triggering during acquisition of US images of the upper GI tract. Molin et al [25] also concluded that ECG triggering during 3D-ES acquisition increased image resolution by reducing tissue dislocation caused by cardiac movements and resulted in improved accuracy in evaluation of smaller superficial lesions in the upper GI tract.…”
Section: Abdominal Imagingmentioning
confidence: 99%
“…In this issue of Abdominal Imaging, Hunerbein et al [21] present an interesting paper on 3D-ES as a new diagnostic modality for the evaluation of GI tumors. They have used a computer-assisted pullback of radial-scanning US catheters to obtain a series of parallel 2D images that were subject to spatial reconstruction and postprocessing in a PC-based workstation.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Enumerating the advantages of 3D-EUS, Huberbein et al 17 pointed out that relationships of the tumor to vessels and other landmarks were delineated more clearly, lymph nodes were easily distinguished from other structures, longitudinal views improved the detection of submucosal infiltration by esophageal cancer, and the relationships of rectal cancer to the sphincter could be visualized more accurately. Kallimanis et al 12 reported that 3D-EUS was advantageous as a global view, providing high-resolution images and improving the recognition of the origin and extent of lesions.…”
mentioning
confidence: 99%
“…Huberbein et al 17 stressed the importance in 3D reconstruction of an optimal distance between the 2D images obtained, defining this distance as 0.1 to 0.3 mm. Small distances between steps result in artifacts, because probe pullback time becomes too long.…”
mentioning
confidence: 99%